The EU ban on the import of seal products and the WTO regulations: neglected human rights of the Arctic indigenous peoples? - Hossain, Kamrul (Polar Record, 2012)
ABSTRACT The EU ban on the import and commercialising of seals and seal products in the EU market, has attracted intense attention in recent years. As seal products mostly originate from outside the EU, it is argued that the EU action has been discriminatory and hence contrary to the WTO regulations. Canada and Norway have been critical of the EU regulation and have initiated dispute settlement procedures within the WTO since most of the products that enter into the internal market are mainly from these countries. The ban also provoked anger within the Inuit and other indigenous communities, mainly from Canada and Greenland. Although the EU regulation provides an exception for Inuit and indigenous hunts and the subsequent commercialisation of resulting products into the internal market, the exception suffers from clarity and lacks proper implementation procedures. The regulation is predicted to lead to the ultimate disappearance of the seal market in the EU, which directly affects the Inuit and other indigenous peoples engaged in sealing activities. They may lose their means of subsistence. While analysing the critical issues concerning the EU and the WTO regulations and its exceptions, the article focuses on the human rights perspective of the Arctic indigenous peoples affected by the EU ban.